Continuity of Midwifery Care for Pregnancy, Childbirth, Postpartum, and Newborns: Kelanjutan Pelayanan Kebidanan untuk Kehamilan, Persalinan, Pasca Persalinan, dan Bayi Baru Lahir - Lestari, Fita Dian; Hanum, Sri Mukhodim Farida (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Maternal and infant mortality remain critical public health challenges worldwide and in Indonesia, requiring continuous and integrated healthcare services. Specific Background: Comprehensive midwifery care from pregnancy through postpartum and family planning is essential to reduce risks of maternal and neonatal complications. Knowledge Gap: Despite the recognition of Continuity of Care (CoC) as a standard approach, limited case-based documentation from Indonesian hospital settings exists, particularly in managing high-risk conditions such as positive HBsAg. Aim: This study aims to describe the implementation of continuity midwifery care provided to a pregnant woman at Rahman Rahim Hospital, Sidoarjo. Results: Using a descriptive case study from May to July 2024, midwifery care included pregnancy management, spontaneous delivery using 60 APN steps, newborn care with immediate immunization, postpartum monitoring, and contraceptive counseling. The client, diagnosed with positive HBsAg, underwent safe delivery, and her newborn received HBIG and Hepatitis B vaccination to prevent vertical transmission. Novelty: This study highlights the application of structured continuity care in a clinical setting while addressing infectious disease concerns. Implications: Findings confirm that continuous and comprehensive midwifery care can reduce maternal and infant risks, strengthen clinical practice, and support national health goals to lower maternal and neonatal mortality rates. Highlights: Structured continuity of care improved maternal and neonatal outcomes Case study addressed high-risk pregnancy with HBsAg positive status Integration of delivery, postpartum, newborn, and family planning care Keywords: Continuity of Care, Midwifery, Pregnancy, Postpartum, Newborn